Mantle Cell Lymphoma Presenting as Multiple Lymphomatous Polyposis of the Colon - Syed Shafiq (Journal of Digestive Endoscopy, 2020)
Mantle cell lymphoma (MCL) is a subset of B-cell non-Hodgkin’s lymphoma with a tendency to involve the gastrointestinal (GI) tract and presents as multiple lymphomatous polyposis of one or multiple segments of the GI tract. Here, we report an unusual case of a 58-year-old female presenting with chief complaints of constipation, bleed per rectum, and unintentional weight loss of 15 kg over 6 months. Colonoscopy revealed the entire colon to be studded with polypoidal lesions of varying sizes which were biopsied. Histopathological examination and immunohistochemistry confirmed the polypoidal lesions to represent MCL. Computed tomography scan showed numerous variable-sized polypoidal lesions scattered throughout the entire colon along with paraaortic and mesenteric lymphadenopathy. Thus far, she has undergone three cycles of chemotherapy with R-CHOP resulting in significant tumor reduction and symptomatic improvement in her well-being.